Design of an IoT-Based Airside Vehicle Tracking System Using GPS–LoRa with an Early Warning Feature at Class III Maimun Saleh Airport - Lulu Salsitiara; Muh Wildan; Johan Wahyudi (Journal of Engineering, Electrical and Informatics, 2026)
This research aims to design and implement an Internet of Things (IoT)-based airside vehicle mon-itoring system at UPBU Maimun Saleh Sabang. The main problem addressed in this study is the absence of a digital monitoring system for operational vehicles, which causes airside supervision to rely solely on manual observation and increases the risk of safety area violations. The proposed system utilizes an ESP32 microcontroller as the main controller, a GPS module for determining vehicle positions, and LoRa communication as an efficient long-range data transmission medium. Vehicle position data are transmitted using the MQTT protocol and visualized in real time through a web-based dashboard. In addition, LED and buzzer indicators function as early warning systems to alert operators when vehicles exceed operational boundaries (geofencing) or predefined speed limits. This study adopts the Research and Development (R&D) method, which includes stages of problem identification, data collection, product design, design validation, design revision, and product testing. The test results show that the system is capable of displaying vehicle positions with an accuracy of approximately ±2 meters and an average latency of 1.5 seconds. Furthermore, the early warning indicators operate effectively in detecting violations of operational area boundaries and speed limits, making the system suitable as an initial prototype to improve safety and efficiency in monitoring airside vehicle movements at Maimun Saleh Airport Sabang.